Political Parties' Right To Recall Against Legislative Members In The Perspective Of A Democratic Rule Of Law - Asriyani, Asriyani; Safrin, Mohamad; Muflih, Muhammad Naufal (Widya Yuridika, 2024)
This article is entitled "Examination of the Recall Rights of Political Parties Against Legislative Members in the Perspective of a Democratic Rule of Law (Case Study of Regional People's Representative Assembly in Central Sulawesi)", where the author will analyze the right of recall or a right that political parties have to temporarily dismiss legislative members at the suggestion of a political party which supports it concerning the principles of a democratic rule of law. The legal issue raised in this writing is "Is the Right to Recall Political Parties Against Legislative Members Compliant with the Principles of a Democratic Rule of Law? ". This article uses normative juridical and empirical juridical research methods by analyzing the rights contained in the Constitution of the Republic of Indonesia and their relationship to Law Number 17 of 2014 concerning the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council, and the Representative Council Regional People, especially those related to the temporary dismissal of legislative members proposed by political parties, in this case is contained in Article 239 paragraph (2) letter "d". In this article, the recall rights of political parties follow the principles of the rule of law. Recalls are needed to monitor political parties over their members who have served as members of the legislature. However, its application still requires clarity regarding matters that result in the recall of a legislative member by his political party.